The effect of training status on the serum creatine kinase response, soreness and muscle function following resistance exercise - Vincent, H. K.; Vincent, K. R. (International Journal of Sports Medicine, 1997)
Untrained individuals develop muscle soreness and increased serum creatine kinase (CK) activity in the blood after strenuous, unaccustomed exercise. An unpublished observation in our laboratory revealed that trained weightlifters also experience considerable soreness after unaccustomed exercise, but may not show a dramatic CK response. This study examined the CK and soreness responses to strenuous exercise in weightlifters (TR, n = 10) and untrained subjects (UTR, n = 10). Trained subjects had a minimum of three years weightlifting experience, and regularly performed squats and leg presses. Untrained subjects had not participated in any regular resistance exercise for the past three years. Following two acclimation sessions, subjects reported to the lab on seven consecutive days and on the tenth day after knee extensor exercise. Weight training sessions occurred on day 1 for the knee extensors (KE) and day 2 for the knee flexors (KF). The weight training consisted of these exercises (sets): squat (5), leg press (3), leg extension and lunge (3) for the KE, double leg curls (6), single leg curls (3), stiff-legged deadlifts (4, TR group only) for the KF at 12 RM for all exercises. To document the stress due to exercise, the loss in strength (isometric peak torque, IPT) was assessed on a Biodex isokinetic dynamometer. Maximal voluntary IPT of the KE at 90 degrees and the KF at 80 degrees decreased 17-30% with no significant differences between groups. Muscle soreness during simulated squat leg curl movement was assessed by a 100 mm visual analog scale (VAS). Average peak KE soreness was 76 mm for TR and 58 mm for UTR, KF soreness was 60 mm for TR and 47 mm for UTR post-exercise. Serum CK levels were significantly different between groups with a peak of 1349 IU for TR and 3272 IU for the UTR (p < 0.01). Although the TR group experienced greater soreness than the UTR, peak serum CK activity was significantly lower, suggesting that trained individuals can develop severe soreness without the same degree of increase in serum CK activity observed in untrained individuals.